RETRACTED: Role of Alterations in Protein Kinase p38γ in the Pathogenesis of the Synaptic Pathology in Dementia With Lewy Bodies and α-Synuclein Transgenic Models - Iba, Michiyo; Kim, Changyoun; Florio, Jazmin; Mante, Michael; Adame, Anthony; Rockenstein, Edward; Kwon, Somin; Rissman, Robert; Masliah, Eliezer (Frontiers in Neuroscience, 2020)
Progressive accumulation of the presynaptic protein -synuclein (-syn) has been strongly associated with the pathogenesis of neurodegenerative disorders of the aging population such as Alzheimer’s disease (AD), Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy. While the precise mechanisms are not fully understood, alterations in kinase pathways including that of mitogen activated protein kinase (MAPK) p38 have been proposed to play a role. In AD, p38 activation has been linked to neuro-inflammation while alterations in p38 have been associated with tau phosphorylation. Although p38 has been studied in AD, less is known about its role in DLB/PD and other -synucleinopathies. For this purpose, we investigated the expression of the p38 family in brains from -syn overexpressing transgenic mice (-syn Tg: Line 61) and patients with DLB/PD. Immunohistochemical analysis revealed that in healthy human controls and non-Tg mice, p38 associated with neurons and astroglial cells and p38 localized to pre-synaptic terminals. In DLB and -syn Tg brains, however, p38 levels were increased in astroglial cells while p38 immunostaining was redistributed from the synaptic terminals to the neuronal cell bodies. Double immunolabeling further showed that p38 colocalized with -syn aggregates in DLB patients, and immunoblot and qPCR analysis confirmed the increased levels of p38 and p38. 1-syntrophin, a synaptic target of p38, was present in the neuropil and some neuronal cell bodies in human controls and non-Tg mice. In DLB and and Tg mice, however, 1-syntrophin was decreased in the neuropil and instead colocalized with -syn in intra-neuronal inclusions. In agreement with these findings, in vitro studies showed that -syn co-immunoprecipitates with p38, but not p38. These results suggest that -syn might interfere with the p38 pathway and play a role in the mechanisms of synaptic dysfunction in DLB/PD.